Dialogues between agroecology and health promotion - Thaisa Santos Navolar; Silvia do Amaral Rigon; Jane Maria de Souza Philippi (Universidade de Fortaleza, 2010)
Objective: To identify aspects that relates ecological family farming and health promotion of farmers belonging to the Association for the Development of Agroecology in Paraná - AOPA. Methods: A qualitative and exploratory research. Semi-structured interviews were conducted during October-November 2007, with six of AOPA farmers, based on an interview guide with questions about the factors that motivated the transition to agroecology and on the perception of participants on possible changes in diet and the health of families related to the insertion in this productive system. Results: We observed that the main reasons for transition to agroecology were issues related to health, especially the occurrence of pesticide poisoning. About the health of families, were emphasized both self care and the use of natural health practices. In relation to family feeding, it was registered the increase of food production for consumption. Conclusion: According to the perception of farmers were identified relevant issues and in line with some of the fields of Health Promotion, particularly linked to the creation of a favorable environment for the development of personal abilities and reinforcement of community action, which indicate that the practice of ecological family farming can be considered an action of health promotion for the farmers and their families.